Growth and growth factors in diabetes mellitus. Issue 1 (January 1987) - Salardi, S; Tonioli, S; Tassoni, P; Tellarini, M; Mazzanti, L; Cacciari, E
Abstract : Growth of 79 children with diabetes was analysed at diagnosis and again after one to 10.7 years of treatment with insulin. Both sexes were tall at onset, whereas at the last observation boys alone showed significant growth retardation. Height standard deviation score (SDS), however, showed no significant fall either in 32 subjects reassessed after five years of disease or in 18 subjects examined at full stature. Skeletal maturity was not significantly impaired after treatment. Pubertal growth spurt was reduced, especially in girls and in subjects with onset of disease at or around puberty. We found no significant correlation between height and height velocity SDS and glycosylated haemoglobin values or secretion of growth hormone during the arginine test. Somatomedin C values were correlated with height velocity SDS in prepubertal boys. The results of this study suggest that there are interferences in the growth of children with diabetes but that they do not seem to have a significant influence on adult height.